The displaced plantation workers: A case study of rubber estates in Kedah - Subramaniam, Shri Dewi; Golam Hassan, Asan Ali; Mohd Mustafa, Muszafarshah (Universiti Utara Malaysia, 2008)
Eviction of plantation workers, due to the development of estate lands and changing land ownerships, has been a big and unresolved issue. Many plantation areas have been sold to make way either for housing projects or industrial sites. When an estate is sold, the estate workers lose not only their jobs, but also their homes and additional sources of income from farming and animal husbandry. They are also entitled to receive termination benefits. The majority of these displaced workers have skills only in the agricultural sector and many of them are old aged. The main objective of this study was to analysis the socioeconomic situations of the displaced workers due to the development of the rubber estate lands in Kedah. The snowball sampling method was used to identify the respondents. The survey was based on 11 estates and 349 ex-workers of these estates were interviewed. The areas of this study were in Sungai Petani and Kulim. The results clearly showed that the majority of the evicted workers migrated to locations that were on average around 3km from their original estates. The majority of them worked with private sector companies upon their evictions. However, many of them are still in their estate houses, waiting for better compensation to be paid in the form of new houses elsewhere. It is suggested in this paper that the compensation should be in terms of home ownership, provided jointly by the government and firms. There have also been some suggestions to solve the issue through programmes provided by the Ministry of Agriculture.